The fall guy [videorecording (DVD)] - Larson, Glen A. (Universal, 2024)
He's a stuntman, and like everyone in the stunt community, he gets blown up, shot, crashed, thrown through windows and dropped from the highest of heights, all for our entertainment. And now, fresh off an almost career-ending accident, this working-class hero has to track down a missing movie star, solve a conspiracy and try to win back the love of his life while still doing his day job.